Analytical Solution of Schrödinger Equation of the Harmonic Oscillator System with Position Dependent Mass Using Transformation Method - Tis Sutisna (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2009)
The Schrodinger equation with position-dependent mass (PDM) becomes one of interesting subjects in the study of quantum systems, because of its wide applications in many physical problems. Meanwhile, harmonic oscillator becomes important model in most physical problems. In this paper, analytical solutions of the PDM Schrodinger equation, i.e. energy eigenvalues En and eigenfunctions , of a one dimensional harmonic oscillator system using transformation method has been studied. The results showed that there was no difference between the energy eigenvalues, En of the harmonic oscillator systems with and without PDM, whereas it is not for the eigenfunctions, of these two harmonic oscillator systems. This difference was due to the presence of dimensionless mass function and the changes of x becomes variable for the eigenfunctions of the harmonic oscillator system with PDM. Moreover, the differences in the eigenfunctions will affect the dynamical properties of the quantum systems. It can be concluded that the harmonic oscillator system with PDM is the generalization of the harmonic oscillator system with constant mass.